2020
DOI: 10.1101/2020.05.24.20112326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Impact of COVID-19 Pandemic on Paediatric Surgical Practice in Nigeria: a National Survey of Paediatric Surgeons

Abstract: Introduction The novel Coronavirus disease has had significant impact on healthcare globally. Knowledge of this virus is evolving, definitive care is not yet known, and mortality is increasing. We assessed its initial impact on paediatric surgical practice in Nigeria, creating a benchmark for recommendations and future reference. Methods Survey of 120 paediatric surgeons from 50 centres to assess socio-demographics and specific domains of impact of COVID-19 on their services and training in Nigeria. Seventy fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…The lockdown period in his study was characterized by a sudden decrease in the number of cleft care services offered at LUTH and this finding is similar to that from other studies where there was a sudden reduction in their respective health care service during the COVID-19 pandemic. 12,22,[27][28][29][30] This was due to the suspension of all healthcare services considered non-urgent and non-essential because of the need to maintain social distancing and reduce the risk of transmission of COVID-19. This also ensures that human and material resources were judiciously channeled toward the management of the COVID-19 pandemic and non-COVID-19 emergency conditions that will require medical attention regardless of the presence of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lockdown period in his study was characterized by a sudden decrease in the number of cleft care services offered at LUTH and this finding is similar to that from other studies where there was a sudden reduction in their respective health care service during the COVID-19 pandemic. 12,22,[27][28][29][30] This was due to the suspension of all healthcare services considered non-urgent and non-essential because of the need to maintain social distancing and reduce the risk of transmission of COVID-19. This also ensures that human and material resources were judiciously channeled toward the management of the COVID-19 pandemic and non-COVID-19 emergency conditions that will require medical attention regardless of the presence of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to studies carried out during the early stages of the pandemic where poor understanding of the novel virus microbiology and transmission and the shortage of PPE lead to the cancellation of surgical operations in the face of rising COVID-19 cases. 22,27 The return of orthodontic interventions was found out to have a more rapid surge than return of surgical services. This surge is likely due to the backlog of patients needing orthodontic care and new patients with orofacial clefts coming in for orthodontic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, hospitals had to adopt measures aimed at reducing the spread of the virus. These included reduction of the workforce present at any point in time, social distancing, deployment of surgical residents to infectious disease units [10], and suspension of elective out-patient activities [11]. Secondly, patients that would have otherwise presented for non-urgent surgical care, elected to remain at home.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Ogundele et al revealed the necessity of developing electronic health in pediatric surgery after the SARS-CoV-2 was necessary. There was a termination of elective surgeries in Nigeria and an enormous decline in emergency surgeries performed on toddlers [ 50 ]. The reason why surgeons are not attending to their duties is that they do not feel safe operating on patients, especially those who have contracted SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%